2019
DOI: 10.3390/w11030529
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Mechanisms for Sediment Transformation Due to Riverbank Collapse

Abstract: Riverbank erosion is a natural process in rivers that can become exacerbated by direct and indirect human impacts. Unfortunately, riverbank degradation can cause societal impacts such as property loss and sedimentation of in-stream structures, as well as environmental impacts such as water quality impact. The frequency, magnitude, and impact of riverbank collapse events in China and worldwide are forecasted to increase under climate change. To understand and mitigate the risk of riverbank collapse, experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…On the other hand, an increase in H w implies a larger hydrostatic pressure, providing supporting forces that reduce the frequency of bank collapse. Figure 9a shows the correlation between the ratio H b /H w and the normalized bank retreat rate (equation 1 and section 2.3), using data from the present (Figure 4 and Table 4) and previous studies (Patsinghasanee et al, 2017;Qin et al, 2018;Shu et al, 2019;van Dijk et al, 2012;Wells et al, 2013). In the above studies banks are mainly composed of silt and sand, and detailed information of variables for each experiment is shown in Table S1 in the supporting information.…”
Section: Factors Affecting Bank Retreat Rate and C Bcmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, an increase in H w implies a larger hydrostatic pressure, providing supporting forces that reduce the frequency of bank collapse. Figure 9a shows the correlation between the ratio H b /H w and the normalized bank retreat rate (equation 1 and section 2.3), using data from the present (Figure 4 and Table 4) and previous studies (Patsinghasanee et al, 2017;Qin et al, 2018;Shu et al, 2019;van Dijk et al, 2012;Wells et al, 2013). In the above studies banks are mainly composed of silt and sand, and detailed information of variables for each experiment is shown in Table S1 in the supporting information.…”
Section: Factors Affecting Bank Retreat Rate and C Bcmentioning
confidence: 93%
“…Fundings from Postgraduate Research and Practice Innovation Program of Jiangsu Province (KYCX18_0606) and National Natural Science Foundation of China (51739005) are gratefully acknowledged. The data used in this study (Figure 9) are extracted from van Dijk et al (2012) (Doi:https://doi.org/10.1029/2011JF002314), Wells et al (2013) (Doi:https://doi.org/10.1016/j.catena.2012.10.004), Patsinghasanee et al (2017) (Doi:https://doi.org/10.1016/j.jher.2017.04.002), Qin et al (2018) (Doi:https://doi.org/10.1016/j.still.2017.12.008), and Shu et al (2019) (Doi:https://doi.org/10.3390/w11030529).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Longoni et al, 2016;Rinaldi and Darby, 2007;Cashman et al, 2018). Sediment generated by bank erosion may be directly entrained into the flow or deposited on the bed (Grissinger et al, 1991;Shu et al, 2019). The volume and size of material input to the channel will control whether the material aggrades the bed or is transported downstream (Rinaldi and Darby, 2007;Swartenbroekx et al, 2010).…”
Section: Disrupting the Avulsion Cyclementioning
confidence: 99%
“…Studies conducted to date have confirmed that tsunamis and storms have generated washover deposits across beaches or dunes in the last decade [101]. The deposition of sediments therefore continues to alter the morphology of coastal areas after each storm event [102][103][104][105][106][107][108], penetrating into existing material and causing various levels of stratification which vary the permeability of the site. This is another aspect that was beyond the scope of this study but would require the characterization of sedimentary characteristics of varius type of washover successions for multiple coastal tophography configurations, including the beach ridge elevation and backshore tophography.…”
Section: Importance Of Permeability Factorsmentioning
confidence: 98%